BMP-9 is a novel marker for colorectal tumorigenesis undergoing the normal mucosa-adenoma-adenocarcinoma sequence and is associated with colorectal cancer prognosis - Fan, Yinjie (Oncol Lett, 2020)
Depending on the type of cancer, bone morphogenetic protein-9 (BMP-9) can promote or inhibit tumorigenesis; however, the function of BMP-9 in colorectal cancer remains unclear. The aim of the present study was to evaluate the clinicopathological importance of BMP-9 expression in the tumorigenesis of normal colorectal epithelial tissue, and subsequent transformation into adenoma and carcinoma. In addition, the present study aimed to determine the prognostic value of BMP-9 on the survival of patients with colorectal cancer (CRC). A total of 65 patients with pathologically confirmed colorectal adenocarcinoma and a history of adenoma were enrolled. BMP-9 and Ki-67 expression was assessed retrospectively using paraffin-embedded samples of normal colorectal mucosa, colorectal adenoma and CRC obtained from each patient. The prognostic value of BMP-9 expression was analyzed in a group comprising 48 patients with CRC and a mean follow-up duration of 39.1 months. Bioinformatics analyses were performed in order to validate the results of the present study using published CRC datasets. The results from the present study suggested that the expression of BMP-9 gradually increased during the transition from normal mucosa to adenoma and subsequent adenocarcinoma (P<0.05); however, no significant association between the expression levels of BMP-9 and the clinicopathological parameters of patients was reported. Kaplan-Meier analysis revealed that patients with high expression levels of BMP-9 exhibited shorter overall survival rate than those with low levels of expression (54.7 vs. 41.3 months; log-rank test, P<0.05). Furthermore, regardless of tumor location and the presence of blood vessel tumor emboli, the univariate and multivariate analyses indicated that BMP-9 expression may be an independent prognostic factor for the overall survival rate of patients with CRC. The results of the present study suggested that BMP-9 may serve an oncogenic role and possess prognostic value in CRC.